2017
DOI: 10.1039/c7tc02822a
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the effects of interfacial carrier transport layers on device performance and optoelectronic properties of planar perovskite solar cells

Abstract: The performance of perovskite device was found to be influenced by the interface quality and bulk defect activities induced in perovskite grown on HTL during device fabrication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
85
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(97 citation statements)
references
References 68 publications
8
85
1
Order By: Relevance
“…[35] Changes in the Li 1s region are undetectable because of the low response sensitivityf actor of lithium (RSF = 0.025) compared with the other elements (1 to F1s, 0.668 to S2p, and 3.59 to Co 2p). Khadka et al [36] reported similar behavior,m entioning that this can happenb ecause of an umber of factors such as accelerated interfacial recombination,b ulk defect activities, or contact limited transport. In particular,t he atomicp ercentageo f Fi ncreases from 6.5 to 10.9 at.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…[35] Changes in the Li 1s region are undetectable because of the low response sensitivityf actor of lithium (RSF = 0.025) compared with the other elements (1 to F1s, 0.668 to S2p, and 3.59 to Co 2p). Khadka et al [36] reported similar behavior,m entioning that this can happenb ecause of an umber of factors such as accelerated interfacial recombination,b ulk defect activities, or contact limited transport. In particular,t he atomicp ercentageo f Fi ncreases from 6.5 to 10.9 at.…”
Section: Resultsmentioning
confidence: 80%
“…Actually,t his explains why PTAA has been reported to produce very stable cells with minimal PCE losses, even when running at 85 8Cf or 500 h, as these aged devices are then characterized at room temperature. [2] The photovoltaic performance as af unction of temperature showsn os ignificant impact on J sc for the PTAA device but a [36] reported similar behavior,m entioning that this can happenb ecause of an umber of factors such as accelerated interfacial recombination,b ulk defect activities, or contact limited transport. When devices are submitted to high temperatures and then returned back to room temperature, the additivese vaporate and so the mobility of these aged HELs becomes closert o the pristine values.…”
Section: Resultsmentioning
confidence: 93%
“…All these properties of lead halide perovskites are superior to typical Cd‐based quantum dots (QDs). Because of these superior properties, tri‐halide lead perovskites have been widely investigated and employed in modern optoelectronic devices including solar cells, LEDs, and photodetectors . Although, all‐inorganic lead halide perovskite (CsPbX 3 ) NC‐based optoelectronic devices exhibit higher stability compared to their organic–inorganic hybrid counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…The reason for this is shown in the SEM image. The longer the delay time, the smaller the grain size of the perovskite film, the worse the film quality, and the more defects inside the film, so fewer photo-generated carriers are injected into the dense TiO 2 layer in the perovskite absorption layer and the quenching ability of the carriers is weakened [22,23]. We measured significant emissions at 782 nm, 779 nm and 775 nm at 0 s, 5 s and 10 s [24].…”
Section: Resultsmentioning
confidence: 99%